Diagnostic Performance of SARS-CoV-2 Rapid Antigen Test in a Large, German Cohort - Olivier Mboma; Elmar Rieke; Parviz Ahmad-Nejad; Stefan Wirth; Malik Aydin (MDPI AG, 2021)
We assessed the performance of a rapid antigen test (RAT) in everyday clinical practice. Between 1 November 2020 until 1 April 2021 all in-patients at the Helios University Hospital Wuppertal, Germany, as well as the accompanying relatives at the Children's Hospital received a SARS-CoV-2 RAT and a SARS-CoV-2 RT-PCR prior to admission. Out of 3686 patients, 22 (0.6%) subjects were tested positive by RT-PCR and RAT, and 3591 (97.4%) were negative by both methods, showing discordant results: RT-PCR+/RAT− in 58 (1.6%) and RT-PCR−/RAT+ in 15 patients (0.4%). Overall sensitivity and specificity of RAT was 27.5% (95%CI 18.1-38.6%) and 99.6% (95%CI 99.3-99.8%), respectively. The sensitivity was slightly higher in adults (30.4%, 95%CI 18.8-90.9%) than in pediatric subjects (20.8%, 95%CI 7.1-42.2%). False negative RAT had a statistically higher Ct-value (p < 0.001) compared to true positive values, and overall sensitivity increased to 80% [59.3-93.2%] with Ct value < 30. While the sensitivity of the RAT was poor compared with the RT-PCR, the specificity was excellent. However, the sensitivity increased with lower Ct value, and with the right anamnesis the RAT can be a quick and easy approach to distinguish people who are infectious with SARS-CoV-2 from noninfectious people, enabling appropriate triage in clinical practice while waiting for the RT-PCR result.